2002
DOI: 10.1093/jmicro/51.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of MHC class II antigens and cathepsin L by subtypes of cortical epithelial cells in the rat thymus: an immunoelectron microscopic study

Abstract: To better comprehend the thymic microenvironment, it is necessary to identify the antigenic profile of cortical thymic epithelial cells (cTECs) that are involved in the development of major histocompatibility complex (MHC)-restricted T cells. Ultrastructurally, cTECs can be classified into four morphologically distinct subtypes: subcapsular/perivascular (EC1), pale (EC2), intermediate (EC3) and dark (EC4) cells. Several immunohistochemical studies were done on cTECs at the light and electron microscopic levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…is at least remarkable. However, other studies have also shown that precursors of CTSL are found in the cytoplasm of epidermal keratinocytes (Kawada et al, 1997), and in the cytoplasm of cortical thymic epithelial cells (Arudchelvan et al, 2002). It has been coined that AEP, like CTSL, could be secreted from cells under some conditions, and may be active in the pericellular and intracellular environment (Barrett et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…is at least remarkable. However, other studies have also shown that precursors of CTSL are found in the cytoplasm of epidermal keratinocytes (Kawada et al, 1997), and in the cytoplasm of cortical thymic epithelial cells (Arudchelvan et al, 2002). It has been coined that AEP, like CTSL, could be secreted from cells under some conditions, and may be active in the pericellular and intracellular environment (Barrett et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is of great consequence that processing is different between TECs and hemopoietically derived APCs. Importantly, TECs, but not APCs, have been shown to express cathepsin L (77–79), which may potentially influence the peptides presented for positive selection compared to negative selection. It has recently been shown that TCR‐transgenic thymocytes in competition for limited peptides can undergo further TCRα gene rearrangements to produce a receptor that may be selected more efficiently by other thymic self‐peptides (80).…”
Section: Thymocyte Selectionmentioning
confidence: 99%
“…MHC class II molecules are distributed largely on the plasma membrane, with a minority present within the cytoplasmic vacuoles. Additional data regarding the localization of MHC class II in cytoplasmic vacuoles of cTECs have been reported elsewhere (Farr and Sidman, 1984; Arudchelvan et al, 2002). The morphology of the MIICs described in the present study is consistent with that of the cytoplasmic vacuoles described by Nabarra and Andrianarison (1987a) and De Waal and Rademakers (1997).…”
Section: Discussionmentioning
confidence: 61%